Balloon occlusion as an adjunctive technique during sclerotherapy of Puig's classified advanced venous malformations. (October 2021) - Sundararajan, Sri Hari; Ranganathan, Srirajkumar; Shellikeri, Sphoorti; Srinivasan, Abhay; Low, David W; Pukenas, Bryan; Hurst, Robert; Cahill, Anne Marie
Objective: Puig types 2 through 4 venous malformations (VMs) are challenging to treat with sclerotherapy given their robust systemic outflow. Endovenous balloon occlusion offers a means of temporarily occluding systemic venous outflow to allow for more complete sclerotherapy. This study reviews our experience of implementing this technique in patients with Puig advanced (types 2 through 4) VMs. Methods: An IRB approved review of treated venous malformations from 2013–2016 revealed 10 patients fitting inclusion criteria. Patient demographics, pre-procedural imaging, intra-procedural technical parameters, and post-procedural follow-up outcomes were recorded. All patients underwent temporary balloon occlusion of a systemic or major draining vein during sclerotherapy. Embolic agents included n-butyl cyanoacrylate glue, sodium tetradecyl sulfate foam, and coils. Standard 5 French angioplasty balloons ranged from 4 to 8 mm diameter and 2 to 8 cm length depending on vessel requiring occlusion. All patients underwent minimum 3-year follow-up questionnaire administration re-assessing resolution of lesion symptomology and post-procedural quality of life (QoL) measures. Results: Of the 10 VMs treated, 2 were Type 2, 6 were Type 3, and 2 were Type 4. More than one sclerotherapy session was required in 7/10 patients (mean: 2, range: 1–4). Most common sites of VM systemic drainage included subclavian, popliteal, internal/external jugular, and basilic veins. All patients had no indication for further sclerotherapy following adjunctive balloon occlusion. No non-target embolization or immediate post-procedural complications occurred. Follow-up questionnaires (mean interval: 3 years 6 months, range: 3 years–3 years 11 months) confirmed the persistence of embolization effects, improved QoL, and no additional sclerotherapy sessions for all patients in the cohort. Conclusions: Endovenous balloon occlusion as an adjunct to sclerotherapy can be considered when treating patients with types 2–4 venous malformations. This technique lowers the risk of non-target systemic venous embolization, allowing for operator-driven deeper intralesional sclerosant penetration and subsequently maintained treatment efficacy.